Conditions that Influence Drivers' Yielding Behavior in Turning Vehicles at Intersections with Traffic Signal Controls. (May 2014) - Bourquin, Eugene A.; Emerson, Robert Wall; Sauerburger, Dona; Barlow, Janet M.
Introduction: This study evaluated drivers' delays and yields in response to pedestrian behaviors when making right turns at the onset of a green traffic signal. Methods: Researchers conducted trials at seven sites in the United States. Data were collected ( n = 445) in six conditions: no pedestrian present (control); and a pedestrian: standing with no cane (control), displaying a cane, flagging a cane, putting a hand up toward the driver, or taking a reversible step into the street. Driver delays were recorded in seconds from the onset of the green traffic signal to when the vehicle first moved and when the front bumper crossed the middle of the pedestrian's crosswalk. Results: Regarding driver responses when the vehicle crossed the crosswalk: a cane display was not significantly different from no cane display; the cane-flagging, reversible-step, and hand-up conditions were all significantly better than a cane display; a reversible step was significantly better than both cane flagging and hand up. Analysis of yields found that: a cane display was not significantly different from not displaying a cane; cane flagging, reversible step, and hand up were all significantly better than the cane display; a reversible step was significantly better than both hand up and cane flagging. The greatest effect was the reversible step, which increased drivers' yielding 205% more often than a pedestrian displaying a cane. Implications for practitioners: For drivers to behave appropriately, they must notice the pedestrian and understand the intent to initiate a crossing. The standard practices taught by O&M specialists may not result in substantial yielding by drivers. O&M specialists could develop new and more effective practices based on these results in order to change risks for pedestrians who are blind or visually impaired when crossing many streets.